128k views
13 votes
Factories 54m3n + 81m4n2 b) 15x2y3z + 25x3y2z + 35x2y2z​

User Thoean
by
4.9k points

1 Answer

11 votes

Part a)

Given the expression


54m^3n\:+\:81m^4n^2

Apply exponent rule:
a^(b+c)=a^ba^c


54m^3n\:+\:81m^4n^2=54m^3n+81m^3mnn
m^4n^2=m^3mnn

Rewrite 81 as 3 · 27

Rewrite 54 as 2 · 27


=2\cdot \:27m^3n+3\cdot \:27m^3mnn

Factor out the common term: 27m³n


=27m^3n\left(2+3mn\right)

Therefore,


54m^3n\:+\:81m^4n^2=54m^3n+81m^3mnn=27m^3n\left(2+3mn\right)

Part B)

Given the expression


15x^2y^3z+25x^3y^2z+35x^2y^2z

Apply exponent rule:
a^(b+c)=a^ba^c


15x^2y^3z+25x^3y^2z+35x^2y^2z=15x^2y^2yz+25x^2xy^2z+35x^2y^2z

Rewrite as


=3\cdot \:5y^2x^2zy+5\cdot \:5y^2x^2zx+7\cdot \:5y^2x^2z

Factor out common term 5y²x²z


=5y^2x^2z\left(3y+5x+7\right)

Therefore,


15x^2y^3z+25x^3y^2z+35x^2y^2z=5y^2x^2z\left(3y+5x+7\right)

User Kcpr
by
5.0k points